1999
DOI: 10.1021/cm980644u
|View full text |Cite
|
Sign up to set email alerts
|

XANES Study of Ti Coordination in Heat-Treated (TiO2)x(SiO2)1-x Xerogels

Abstract: Accurate measurements of the height and position of the preedge peak in Ti K-edge XANES (X-ray absorption near-edge structure) can distinguish 4-, 5-, and 6-fold coordination of Ti by O ([4]Ti, [5]Ti, and [6]Ti, respectively), and mixtures thereof. This approach has been applied to titania−silica xerogels, (TiO2) x (SiO2)1 - x , prepared from Si and Ti alkoxides using a prehydrolysis step and acid catalyst, with 0.18 < x < 0.75. As expected, samples with x = 0.75 contain phase-segregated, amorphous, pre-anata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
92
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 30 publications
13
92
2
Order By: Relevance
“…27 Al nuclear magnetic resonance (NMR) results revealed that the proportion of highly coordinated aluminum atoms in this titanium-bearing glass was higher than in the titanium-free sample. RMC modeling was used to interpret the structural role of these [5] Al species and we show a trend for preferential bonding between [5] Al and Ti atoms. This favored linkage is important to understand the role of titanium dioxide as a nucleating agent in inorganic glass-ceramics fabrication.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…27 Al nuclear magnetic resonance (NMR) results revealed that the proportion of highly coordinated aluminum atoms in this titanium-bearing glass was higher than in the titanium-free sample. RMC modeling was used to interpret the structural role of these [5] Al species and we show a trend for preferential bonding between [5] Al and Ti atoms. This favored linkage is important to understand the role of titanium dioxide as a nucleating agent in inorganic glass-ceramics fabrication.…”
Section: Introductionmentioning
confidence: 88%
“…In the COR glass, enough Mg 2+ ions are present to charge-compensate the negative charge of the aluminate tetrahedra and, looking only to the glass composition, all aluminum atoms are expected to be [4] Al. However, it appears that significant amounts of [5] Al Figure 5. 27 Al 1D NMR experimental spectra and the fitting models obtained with parameters given in table 2 (top) and contour plots of 27 Al MQ-MAS NMR spectra (bottom) for the (a) 2MgO-2Al 2 O 3 -5SiO 2 (COR) glass and for the (b) 2MgO-2Al 2 O 3 -5SiO 2 -TiO 2 (Ti-COR) glass.…”
Section: X-ray Diffraction Datamentioning
confidence: 99%
See 3 more Smart Citations